Respiratory Health Effects of Air Pollution and Climate Parameters in the Population of Drobeta Turnu-Severin, Romania - Petrescu, Cristina; Suciu, Oana; Ionovici, Romanita; Herbarth, Olf; Franck, Ulrich; Schlink, Uwe (IntechOpen, 2011)
None